Performance of Floriculture Industry in East Africa: What Lessons can Tanzania Learn from Kenya? - Mwase, Donatha E. (Asian Business Review, 2015)
In the recent days Sub-Saharan African counties look at floriculture as a viable alternative to boost their foreign earnings through export of cut flowers. However, while the sector is second largest contributor to foreign earnings for Kenya, Tanzania is yet to fully exploit the potential for both production and export of cut flowers. This paper was set with an aim to make comparative assessment of performance of floriculture industries in Kenya and Tanzania. The study relied mainly on secondary data obtained from International Trade Centre (ITC) database, published previous survey reports and several national policies and strategies. The findings revealed that Kenya was performing better than Tanzania in terms of quantity of cut flowers exported to different destinations in the World and in-terms of value of earnings from export of those flowers. It was observed that while the floriculture sector for both countries had been growing in the past nine years, Kenya’s performance was far beyond Tanzania’s. Among the major hurdles to the growth of Tanzania’s floriculture industry included lack of efficient air transportation, absence of a National Horticulture Policy in place, unorganized farming systems without clusters and foreigners domination of the sector. The paper recommended for a number of measures to improve performance of floriculture industry in Tanzania including need to: (a) formulate national horticulture policy to guide expansion of the sector (b)engage in strategic negotiations with big cargo Airline Companies so that they can frequently land at Kilimanjaro International Airport for easy transportation of cut flowers to the different destinations in the world and (c) launch coordinated efforts by experts from the Tanzania’s ministries of agriculture, trade, transportation and finance to draw lessons from Kenya on how to grow floriculture in the country.
Keywords: Floriculture; Performance; Kenya; Tanzania; Lessons